Implementasi Projek Ecobrick Sebagai Pemanfaatan Sampah Plastik Di SDN Calengka - Citra Resmi Rahayu (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
In the Calengka Elementary School environment, there is a lot of plastic waste from student snack packaging which usually ends up in the trash and is burned, causing air pollution and toxic gases that pollute the environment. Therefore, there is an ecobrick innovation which is carried out as a form of dedication for teaching campus students which is a solution for utilizing plastic waste at SDN Calengka. The aim of this research is to describe the implementation of making Ecobricks for fifth grade students at SDN Calengka, analyze the challenges faced in the making process, and assess the impact of this implementation on students. This research uses a qualitative approach with the Action Research method which is carried out in several stages, namely planning, action, observation and reflection. The ecobrick program at SDN Calengka, initiated by Teaching Campus students, plays an important role in educating students about plastic waste management and providing environmentally friendly solutions. Despite challenges such as a lack of environmental understanding, material collection, and the need for technical skills, the program succeeded in increasing students’ environmental awareness, motor skills, creativity, and cooperation.